The militarization process in Tucumán during the first half of the 19th century: experiences and identities of the popular groups. - Davio, Marisa (Universidad Pedagógica y Tecnológica de Colombia, 2011)
The work analyzes the impact of the militarization of the society from the political changes experienced with the Revolution of May, 1810 in Buenos Aires and their repercussions in Tucumán. The process of institutionalization of the military force reverberated in the interpersonal area in the individuals who took part in the militias and the regular army during the irst half of the 19th century. The popular groups, most of them members of the tropes, had changes in their daily life, in their roles and identities in the socio-politic ield. That led to their participation in the public space and practice series of “tactics” and resistance ways faces up the requirements come from the political power.